The role of digital transformation in improving the efficiency of administrative performance: An applied study at the College of Administration and Economics – University of Fallujah - Ahmed Talal Khalaf Al-isawi (Goodwood Publishing, 2026)
Purpose: This study aims to examine the role of digital transformation in improving the efficiency of administrative performance at the College of Administration and Economics, University of Fallujah. Research Methodology: This study adopted a descriptive-analytical approach. The data collection tool was a questionnaire, which was used to gather responses from the research community consisting of 85 employees and administrators. Owing to the small size of the population, the sample included all members, utilizing the comprehensive enumeration method. Results: The results revealed that digital transformation has a strong and positive impact on the efficiency of administrative work performance. The adoption of digital systems, development of digital skills, and automation of administrative processes were key factors in improving speed, accuracy, resource utilization, and user satisfaction. Conclusions: This study concludes that digital transformation significantly enhances administrative performance by improving work speed and precision, optimizing resource use, and increasing beneficiary satisfaction. These improvements result from the adoption of digital systems, enhancement of digital skills, and automation of administrative tasks. Limitations: Although this study provides valuable insights into the impact of digital transformation on administrative performance, the research was limited to the College of Administration and Economics at the University of Fallujah, meaning that the results may not be generalizable to other institutions or contexts. Contributions: This study contributes to the understanding of how digital transformation influences administrative performance. It provides practical recommendations for enhancing digital transformation in colleges to improve administrative efficiency and facilitate decision-making.